Indonesian–English translanguaging practices in bilingual classroom : Distribution and functions in elementary education - Dhanesvar Karel Noveintine; Adi Sutrisno (Universitas Muhammadiyah Purwokerto, 2026)
English is commonly positioned as the language of instruction in Indonesian bilingual schools, but classroom interaction often reflects the simultaneous use of Indonesian and English to support teaching and learning. This study addresses the translanguaging phenomenon as a flexible practice that allows teachers and students to use both languages as an integrated system. This study aims to examine the distribution of translanguaging utterances compared to monolingual use and to identify the specific functions of translanguaging in classroom activities. The study utilized a mixed-methods design; data were collected through audio recordings and observations of teachers and students in upper classes, grades 4 to 6, in a selected bilingual elementary school in Yogyakarta. Grades 4 to 6 were selected because students at this level demonstrate more stable bilingual development and engage in classroom interaction using both languages. Interactions between teachers and students were transcribed and coded into Indonesian-only, English-only, and translanguaging units based on turn-taking. The coded transcription of translanguaging is continuously categorized into several functions based on the utterances. The research design combined quantitative calculations of language distribution with qualitative discourse analysis of interactional units. The findings indicate a balanced linguistic distribution with Indonesian only (37%), English only (35%), and translanguaging (28%). Furthermore, the study identified six functions of translanguaging, i.e., Conceptual Explanation (41%), Meaning Negotiation (24%), Participant Management (11%), Procedural Instruction (10%), Classroom Management (8%), and Interpersonal Clarity (6%). These findings contribute to bilingual education by demonstrating that translanguaging is a purposeful, functional, and supportive practice that increases conceptual understanding and encourages inclusive participation. This research confirms that translanguaging acts as a significant tool that enhances the quality of bilingual learning environments, particularly in Indonesian and English languages.